1997
DOI: 10.1152/ajpheart.1997.273.5.h2458
|View full text |Cite
|
Sign up to set email alerts
|

ATP-sensitive potassium channel mediates delayed ischemic protection by heat stress in rabbit heart

Abstract: Heat shock protects against myocardial ischemia-reperfusion injury possibly via increased expression of heat shock proteins. The direct evidence of heat shock protein protection in vivo remains circumstantial, and no other new mechanism of protection has been proposed. Recent studies suggest that opening of ATP-sensitive K+ channels (KATP channels) plays an important role in ischemic preconditioning; however, it is not known whether this channel is also important in delayed protection conferred by heat shock. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 29 publications
2
62
1
2
Order By: Relevance
“…The impaired channels could be linked to the failure to enhance HSP expression in diabetes. However, it has been shown in the rabbit that heat stress confers cardioprotection and that blockade of the K ATP channels with their blockers during ischaemia and reperfusion abolishes the effect of heat stress on cardioprotection, but not on HSP72 expression [5], indicating the cardioprotective action of HSP might not directly link to the channels. We have also shown that PKC-ε mediates delayed cardioprotection of UP [21].…”
Section: Discussionmentioning
confidence: 99%
“…The impaired channels could be linked to the failure to enhance HSP expression in diabetes. However, it has been shown in the rabbit that heat stress confers cardioprotection and that blockade of the K ATP channels with their blockers during ischaemia and reperfusion abolishes the effect of heat stress on cardioprotection, but not on HSP72 expression [5], indicating the cardioprotective action of HSP might not directly link to the channels. We have also shown that PKC-ε mediates delayed cardioprotection of UP [21].…”
Section: Discussionmentioning
confidence: 99%
“…These improvements in energy metabolism with heat shock treatment of hearts before I/R are associated with enhanced recovery in myocardial performance and reduced I/R injury. Also, a decrease in the duration of cardiomyocyte action potentials secondary to an increase in activity of ATP-sensitive potassium channels (12,27) and diminished accumulation of intracellular Ca 2ϩ (45) with resulting reduced Ca 2ϩ sensitivity (22) have been reported to be induced by heat stress and to limit I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Reactions were terminated by the addition of SDS Laemmli sample buffer at 90 • C. Samples were then heated for 5 min and subjected to SDS/PAGE. [8][9][10][11][12][13][14][15][16][17]] These peptides were then conjugated to the protein transducing domain of the HIV-Tat protein (amino acids 47-57) as described previously [37]. An HIV-Tat carrier-carrier peptide (YGRKKRRQRRR-YGRKKRRQRRR) was synthesized as a control.…”
Section: In Vitro Phosphorylation Assaysmentioning
confidence: 99%
“…Experimentally, it is the most powerful form of cardiac protection known and it has been demonstrated in cardiac myocytes [2][3][4][5], intact hearts [6,7] and many animal species [8][9][10][11], including humans [12][13][14]. Downstream signalling molecules reported to be involved in PC include ATPdependent potassium channels [4,12,15,16], PKC (protein kinase C) isoenzymes [2, 3,12,15,17,18], MAPK (mitogen-activated protein kinase) enzymes [19][20][21], tyrosine kinases [22][23][24], PI3K (phosphoinositide 3-kinase) [22,25], heat-shock proteins [5,16,26], nitric oxide [27][28][29], free radicals [21,25,30] etc.…”
Section: Introductionmentioning
confidence: 99%